Chinese families' knowledge, attitudes, and practices regarding seizure management for children with epilepsy: a mixed-methods study - Cui, Cui; Li, Shuangzi; Chen, Wenjin; Zhou, Hengyu; Zheng, Xianlan (Frontiers in Public Health, 2023)
Objective This study aimed to examine Chinese families' knowledge, attitudes, and practices regarding the management of acute seizures (AS) that occur outside the hospital in children with epilepsy (CWE) and factors that influence AS. Design A mixed-methods sequential explanatory study was conducted, which was integrated at the design and methods levels. In phase 1, a questionnaire was developed for this study, and a family functioning assessment was administered from Nov 2021 to Apr 2022. Multivariate logistic regression was used to analyze the knowledge, attitudes, and practices (KAP) and factors that influence AS. In phase 2, family caregivers (FCGs) were recruited from Jul to Aug 2022 to participate in a qualitative exploration, using semi-structured interviews and a combination of inductive and deductive methods. Setting The setting was five children's specialty hospitals in different regions of China. Participants The participants were FCGs of CWE. A total of 645 participants were included in the quantitative phase, and 15 FCGs (eight parents, five grandparents, and two others) were recruited for the qualitative phase. Results The FCGs' average total KAP score for AS management was 66.23 ± 15.12, with 45.42% of FCGs having a low level. Univariate and multivariate regression analyses showed that demographic factors, disease characteristics, and family function significantly predicted family management of AS. The three most salient themes and eight sub-themes from phase 2 were explored. The quantitative and qualitative databases were analyzed separately and combined through integration, and a conceptual model was constructed based on the individual and family self-management theory (IFSMT); the model consisted of context, knowledge, self-regulation, and promotion factors. Conclusion Chinese families have a positive attitude toward the management of out-of-hospital AS in CWE, but lack practice and related knowledge. AS management for CWE families was associated with the demographic characteristics of FCGs, epilepsy, and family characteristics. The research findings expand the existing application requirements of an Acute Seizure Action Plan and patient safety. Our results also indicate a pressing need for localized development of AS emergency medicine in family medicine, the establishment of auxiliary information systems, the utilization of caregivers' positive psychological resources, and improvements in family function for intergenerational care.